DERIVING THE EXACT FORMULA FOR PERIMETER OF AN ELLIPSE USING COORDINATE TRANSFORMATION - Harun Abdul Rohman (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2022)
The ellipse can be transformed into a circle by dilating the coordinates of the ellipse relative to the x-axis and y-axis. Therefore, this study aimed to derive the formula for the equation of the perimeter of an ellipse by using the transformation of an ellipse to a circle. This transformation was arranged so that the perimeter of the ellipse was equal to the perimeter of the circle. The type of research was in the review of books, articles, and relevant research reports. The results showed that the ellipse can be transformed into a circle while maintaining its perimeter. So, the perimeter of the ellipse was the same as the perimeter of the circle.